City Branding sebagai Upaya Mendukung Pemulihan Perekonomian dan Pariwisata Sumatera Barat di Masa Pandemi Covid-19 - Diah Austin; Haiyyu Darman Moenir; Zulkifli Harza; Elfitra Elfitra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The spread of the COVID-19 virus that hit the world in 2019 has significantly impacted life, including the creative economy and tourism sectors in West Sumatra. The pandemic conditions have caused a decrease in the number of foreign and domestic tourist visits. This decline has a direct impact on hotel occupancy in West Sumatra. SMK Negeri 9 Padang is a vocational school with a tourism and hospitality program that has an essential role in developing tourism in West Sumatra in the future through the contribution of its graduates. Socialization of the importance of building a city brand to students of SMK Negeri 9 Padang aims to provide students with knowledge in interacting and promoting in the digital era as tourism actors and connoisseurs to increase the number of tourist visits and support economic recovery. Activities involved material presentation methods, interactive discussions, and case analysis presentations. The activity resulted in an increase in knowledge and a change in students' perspective on promoting tourism in West Sumatra. Before being given socialization, students needed to understand the importance of city branding for tourism. After being given socialization, students have good knowledge and understanding of the importance of branding in promoting tourism in West Sumatra.